2020
DOI: 10.1101/2020.11.04.20226233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of an Ozone Disinfecting and Sanitizing Cabinet to Decontaminate a Surrogate Virus for SARS-CoV-2 on N-95 Masks

Abstract: Medical demands during the COVID-19 pandemic have triggered a grave shortage of medical-grade personal protective equipment (PPE), especially, N95 respirators. N95 respirators are critical for the personal protection of medical providers and others when being exposed to individuals with infections caused by the SARS-CoV-2 coronavirus. To address the shortage of N95 respirators, innovative methods are needed to decontaminate coronaviruses from N95 respirators, allowing them to be safely reused by healthcare wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…1) indicate the effectiveness of the ozone-chamber procedure to inactivate both Gram-negative and Gram-positive bacteria. Interestingly, our findings demonstrated that the Gram-positive S. pseudintermedius LBV072/17 was undetectable in a shorter amount of ozone time exposure than the Gram-negative E. coli ATCC 25922, which is in contrast with previous literature that determined a higher ozone sensibility in Gram-negative bacteria [17,21]. Similar results were obtained with face masks experimentally contaminated with influenza A (H 1 N 1 ) virus and Gram-positive Staphylococcus aureus bacteria.…”
Section: Rapid Ozone-based Treatment Is Effective To Disinfect Gram-n...supporting
confidence: 64%
“…1) indicate the effectiveness of the ozone-chamber procedure to inactivate both Gram-negative and Gram-positive bacteria. Interestingly, our findings demonstrated that the Gram-positive S. pseudintermedius LBV072/17 was undetectable in a shorter amount of ozone time exposure than the Gram-negative E. coli ATCC 25922, which is in contrast with previous literature that determined a higher ozone sensibility in Gram-negative bacteria [17,21]. Similar results were obtained with face masks experimentally contaminated with influenza A (H 1 N 1 ) virus and Gram-positive Staphylococcus aureus bacteria.…”
Section: Rapid Ozone-based Treatment Is Effective To Disinfect Gram-n...supporting
confidence: 64%
“…Our study was primarily directed at discovering the potential of ozone in the disinfection of PPE. The promising data from this small-scale investigation on a SARS-CoV2 surrogate virus -MS2 bacteriophage [16] -suggests further studies that may compare ozone to currently employed decontaminants, such as VHP.…”
Section: Discussionmentioning
confidence: 96%
“…Bacterial cells including E. coli (strain C-3000) serve as a host for MS2 bacteriophage. Its small size, icosahedral structure, and environmental resistance have made MS2 ideal for use as a surrogate virus (particularly in place of picornaviruses such as poliovirus and human norovirus) in water quality and disinfectant studies [13][14][15][16]. The respective incubation and phage propagation procedures were obtained from the supporting documentation for each product, and all incubation media were tested for and passed standard sterility tests.…”
Section: Test Microorganismmentioning
confidence: 99%
“…Since all these methods have advantages and disadvantages, a careful consideration of the type of respirator and biological target has to be performed, to restore the fit and filtration capacity of the N95 respirator post decontamination. In this regard, several recent reports have evaluated the effect of ozone treatment on the filtration performance of N95 respirators [ 46 , 72 , 73 , 74 ]. Interestingly, neither higher ozone concentration (200 ppm for 90 min) nor prolonged ozone exposure (20 ppm for 36 h) appear to degrade or damage the filtration efficiency of N95 FFRs, illustrating the effectiveness of ozone treatment for contaminated FFRs regeneration [ 74 ].…”
Section: Discussionmentioning
confidence: 99%